Wimbledon - Bevan, Tim; Fellner, Eric; Chasin, Liza; Richards, Mary; Brooks, Adam 1956-; Flackett, Jennifer; Levin, Mark R. (Mark Reed) 1957-; Loncraine, Richard; Dunst, Kirsten 1982-; Bettany, Paul 1971-; Neill, Sam; Favreau, Jon; et al. (Universal, 2004)
An aging male tennis star has one last shot, and two weeks, to win the greatesst tennis tournament and the heart of an upcoming women's tennis star.